2021
DOI: 10.1192/bjo.2020.172
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-wide SARS-CoV-2 antibody screening of staff in a university psychiatric centre in Belgium

Abstract: In this first serosurvey among psychiatric healthcare providers, only 3.2% of a sample of 431 staff members of a Belgian University Psychiatric Centre, screened 3–17 June 2020, had SARS-CoV-2 immunoglobulin G antibodies, which is considerably lower compared with both the general population and other healthcare workers in Belgium. The low seroprevalence was unexpected, given the limited availability of personal protective equipment and the high amount of COVID-19 symptoms reported by staff members. Importantly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Some studies have not identified an association between SARS-CoV-2 infection in HCP and close contact with COVID-19 patients in the workplace ( 13 18 ). Our analysis, however, showed that assisting COVID-19 patients with ADL was independently associated with being an HCP case.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have not identified an association between SARS-CoV-2 infection in HCP and close contact with COVID-19 patients in the workplace ( 13 18 ). Our analysis, however, showed that assisting COVID-19 patients with ADL was independently associated with being an HCP case.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10]22 A serosurvey of the staff working in mental health services One paper in the thematic series reports the first published serosurvey among psychiatric healthcare providers showing a lower seroprevalence compared with the results from other studies in the general population and other healthcare workers in Belgium. 51 This paper reports 3.2% of psychiatric providers were seropositive, 51 whereas the proportion of staff in a tertiary medical centre were reported as 6.4%. 52 Exposure at home predicted the presence of antibodies, but exposure at work did not.…”
Section: Research Into the Impact On The Mental Health Of Healthcare Staffmentioning
confidence: 97%
“…Compliance with containment measures such as social distancing, disinfection, and mask wearing should be advised; where this is difficult, possible compartmentalization of patients and health-care professionals can be considered. Adequate resources (such as PCR testing, masks, and disinfectants) should be made available to mental healthcare facilities [54]. In general, lockdowns should be avoided: psychiatric patients, and their families, may benefit from regular contact with the outside world, whereas prolonged home confinement may increase the levels of distress and social isolation, also worsening psychiatric symptomatology [55][56][57][58].…”
Section: Inpatient Treatment and Collective Livingmentioning
confidence: 99%